Pengaruh Kemandirian Belajar terhadap Kemampuan Pemecahan Masalah Matematis - Tri Mutia Salsabila; Leonard Leonard; Novita Cahyo Puteri (EduResearch Mitra Inovasi, 2023)
This study aims to determine the effect of learning independence on mathematical problem solving abilities. The sample used in this study was 238 students with random sampling techniques from grade VIII students in the even semester at SMP Negeri 1 Depok and MTs Al Hidayah C.A Depok. The method used in this study is the survey method, data collection is carried out by distributing tests for variables of mathematical problem solving ability and questionnaires for variables of learning independence. Based on hypothesis testing and data analysis, it can be concluded that there is a significant positive influence between learning independence (X) and mathematical problem solving ability (Y). This is evidenced by Fcalculate > Ftable, which is 50.55 > 3.8812. With a determinant coefficient of learning independence on mathematical problem solving ability of 17.64% and 82.36%, the rest is influenced by other variables.